A smartphone controlled handheld light painting application - Teo, Zi Jie (2017)
With the evolution and increasing popularity of DSLR cameras, many creative photographic techniques have been developed and improved. Light painting, also known as “light drawing”, is one such technique which uses a hand-held light source to colour part of the photograph during exposure. Over the years, many creative light painting techniques have been developed and one popular technique involves the user of computerised light painting devices. This project aims to explore and improve on the portability of the former handheld computerised light painting device, as well as to the control the device on the smartphone platform. The light painting devices houses an AVR microcontroller and uses Bluetooth LE technology to establish a form of communication with the Android application. This report provides a detailed documentation on the development of the smartphone controlled hand-held light painting application. It will feature the various aspects and approaches, hardware and software, as well as changes and enhancements along the way leading to the final product.